2017
DOI: 10.1016/j.biopsych.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and Behavioral Changes in Kynurenine 3-Monooxygenase Knockout Mice: Relevance to Psychotic Disorders

Abstract: BACKGROUND Kynurenine 3-monooxygenase (KMO) converts kynurenine to 3-hydroxykynurenine, and its inhibition shunts the kynurenine pathway - which is implicated as dysfunctional in various psychiatric disorders - towards enhanced synthesis of kynurenic acid (KYNA), an antagonist of both α7 nicotinic acetylcholine and NMDA receptors. Possibly as a result of reduced KMO activity, elevated central nervous system levels of KYNA have been found in patients with psychotic disorders, including schizophrenia (SZ). MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 76 publications
(107 reference statements)
4
46
0
Order By: Relevance
“…Remarkably, pharmacological inhibition of KMO in conjunction with L-Kynurenine administration confirmed these observations as we detected a significant dampening of CaMKII phosphorylation in the mPFC and vHip. Since KMO inhibition is known to increase KYNA (Justinova et al, 2013; Moroni et al, 2005), our results supports the hypothesis that excess levels of KYNA possibly contributes to exacerbations in cognitive malfunction (Erhardt et al, 2016; Heisler and O'Connor, 2015). Furthermore, our novel findings promote the possibility that LPS-driven neuroinflammatory signaling contributes to deficits in stimulus processing preferentially through the mPFC.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Remarkably, pharmacological inhibition of KMO in conjunction with L-Kynurenine administration confirmed these observations as we detected a significant dampening of CaMKII phosphorylation in the mPFC and vHip. Since KMO inhibition is known to increase KYNA (Justinova et al, 2013; Moroni et al, 2005), our results supports the hypothesis that excess levels of KYNA possibly contributes to exacerbations in cognitive malfunction (Erhardt et al, 2016; Heisler and O'Connor, 2015). Furthermore, our novel findings promote the possibility that LPS-driven neuroinflammatory signaling contributes to deficits in stimulus processing preferentially through the mPFC.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, our study is the first to show that pharmacological inhibition of KMO, which deviates kynurenine conversion toward KYNA (Erhardt et al, 2004; Justinova et al, 2013; Speciale et al, 1996), can effectively increase PKC-Nrgn phosphorylation in the mPFC. Supporting our findings, KMO null mice, which exhibit increased brain KYNA, also upregulates Nrgn mRNA expression (Erhardt et al, 2016). As with LPS administration, no significant changes to Nrgn signaling was detected in the vHip from KMO inhibition.…”
Section: Discussionsupporting
confidence: 77%
“…Models that support the in uence of the HPA axis on depression postulate chronically dysregulated activation of the HPA axis, which is also associated with dysregulation of immune function [8][9][10][11] . Various animal studies have shown the relationship between depression and in ammation [12][13][14][15] . In a human study, Pedraz-Petrozzi recently showed correlations between the severity of depression, assessed with the BDI-FS 16 , and the pro-in ammatory cytokine TNF-α in people with depression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, systemic administration of a selective KMO inhibitor to the dam during the final prenatal week results in distinct structural and behavioral impairments in the offspring in adolescence and adulthood (Forrest et al, 2013a;Forrest et al, 2013b;Khalil et al, 2014;Pisar et al, 2014), supporting the potential relevance of prenatal KYNA elevations for the emergence of SZ pathology later in life. Notably, we recently found similar biochemical and behavioral abnormalities reminiscent of SZ in adult mice with a complete deletion of the Kmo gene (Kmo -/mice; Erhardt et al, 2017).…”
Section: Introductionmentioning
confidence: 80%